KELAMBATAN WAKTU PENYALAAN CAMPURAN SOLAR DAN METIL ESTER KELAPA SAWIT PADA MOTOR DIESEL INJEKSI LANGSUNG - Prawoto L; Shalahuddin Shalahuddin; R. C Nugroho (Mesin, 2004)
Ignition delay is an important parameter in diesel engine operation. It is defined as the time (or crank angle degree) between the start of injection and the start of combustion. Ignition delay should be kept as short as possible, otherwise diesel knocking can occur if the delay is too long. Many works have shown that increasing fuel cetane number may shorten the ignition delay. In conjunction with the BPBT "“ PPKS Biodiesel Project to utilize methyl ester palm oil (sawit) (MES) as an alternative fuel, several compositions of MES-conventional diesel fuel blends were tested. Cetane number of MES-diesel fuel blends were calculated to be higher than that of conventional diesel fuel. Hence, it was expected that the MES-diesel fuel blends would yield shorter ignition delay than pure diesel fuel. Engine tests were conducted to compare the performance of several blends of MES-diesel fuel. The results from in-cylinder pressure data, from which ignition delay was determined have confirmed this work. Furthermore, correlations between ignition delay, cetane number, and engine speed have been obtained in simple linear equations.Key words: Ignition delay, Cetane number, Biodiesel, Methyl Ester Sawit (MES), Direct injection.